Civil society mobilisation after Cyclone Tracy, Darwin 1974. (1st January 2021) - Handmer, John; Maynard, Pascale
ABSTRACT: Major disasters challenge or exceed the capacity of the official emergency management sector to provide needed rescue services, support and relief. Emergency services in most jurisdictions do not have the surge capacity for unusual or extreme events without drawing on other jurisdictions or local people from outside the formal emergency management organisations. In such circumstances, those in the affected area need to organise themselves and make maximum use of local resources to cope with the immediate aftermath of impact. To find the required surge capacity, this suggests a whole of society response with the official system working with the capacities of people, commerce and organisations outside the emergency sector. An example is provided by the destruction of the northern Australian capital city of Darwin by Cyclone Tracy in December 1974. Informal volunteering and emergent leadership in Darwin and across Australia were critical to the immediate response and relief. Volunteering was widespread and worked well alongside official emergency management. With today's information and communication technologies and a strong national resilience narrative, we would expect to do at least as well. However, governments now exercise much more control over civil society. We examine the implications for surge capacity and adaptability.